1969
DOI: 10.1042/bj1150563
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of deoxyribonucleic acid in rat brain

Abstract: 1. A procedure is given for spectrophotometric analysis of rat brain DNA after its resolution into component bases. Amounts of tissue in the range 50-100mg. can be used. 2. The amount of DNA obtained by the present method is 80% greater than that reported for rat brain by a previous procedure specific for DNA thymine. Identity of the material is established by the base ratios of purines and pyrimidines. The features responsible for the higher yield are the presence of dioxan during alkaline hydrolysis of tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1972
1972
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
(14 reference statements)
1
8
0
Order By: Relevance
“…Samples of fresh, unfixed cortical grey matter yielded 61,217 ± 4,718 nuclei/mg (n=3), which is a major improvement towards the presumed actual number (70,000–122,000) obtained by histology and the IF in our own and other’s previous studies (Table 2). The deficit in numbers, especially from white matter samples, is consistent with the known difficulties in retrieving DNA from lipid-rich tissue, such as white matter (Penn and Suwalski, 1969; Saldanha et al, 1984; Zamenhof et al, 1964). We did not attempt to isolate DNA from the white matter within the cerebellum, due to the small size of white matter tracts in these tissues (Fig.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Samples of fresh, unfixed cortical grey matter yielded 61,217 ± 4,718 nuclei/mg (n=3), which is a major improvement towards the presumed actual number (70,000–122,000) obtained by histology and the IF in our own and other’s previous studies (Table 2). The deficit in numbers, especially from white matter samples, is consistent with the known difficulties in retrieving DNA from lipid-rich tissue, such as white matter (Penn and Suwalski, 1969; Saldanha et al, 1984; Zamenhof et al, 1964). We did not attempt to isolate DNA from the white matter within the cerebellum, due to the small size of white matter tracts in these tissues (Fig.…”
Section: Resultssupporting
confidence: 65%
“…Some of these studies compared DNA content in primate cortex with glial and neuronal densities as obtained by histological techniques (Brizzee et al, 1964; Cragg, 1967; Bass et al, 1971; Ling and Leblond, 1973; Leuba and Garey, 1989). While theoretically an elegant solution (Jacobson, 1991), this approach has been criticized for a number of reasons: (1) many initial reports relied on DNA-P measurement, but P may not necessarily be representative of only DNA (Drasher, 1953); (2) it requires complete DNA extraction; (3) euploidy in brain cells is assumed, yet as many as 20% of adult human neurons are hyperploid (Mosch et al, 2007); (4) DNA extraction is problematic when lipids and lipoproteins are abundant in the tissue of interest, as is the case in white matter (Penn and Suwalski, 1969; Saldanha et al, 1984; Zamenhof et al, 1964); (5) aldehyde fixation causes DNA denaturation (Srinivasan et al, 2002) and possibly irreversible crosslinking of peptides to DNA, thereby decreasing the yield of DNA measurable by spectrophotometry (Savioz et al, 1997). Indeed, variability of DNA extraction is evident by divergent published reports of DNA yields, ranging from 33 μg/g to 970 μg/g (Niland et al., 2012; Saldanha et al 1984; Winick, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…HCl-water (200:100:3:3, by vol.) (Penn & Suwalski, 1969); solvent 8, propan-2-olpyridine-water-acetic acid (8:8:4:1, by vol.) (Gordon et al, 1956); solvent 9, ethyl acetatepyridine-water (5:2:7, by vol.…”
Section: Methodsmentioning
confidence: 99%
“…Attempts to develop a satisfactory procedure based on extraction with concentrated sodium bromide solution (Emanuel & Chaikoff, 1960) appeared to give conventional DNA preparations, but perchloric acid hydrolysis followed by determination of base ratios revealed low cytosine values. This observation and the possibility that the method had preserved a labile DNA fraction usually lost in some analytical methods (Penn & Suwalski, 1969), suggested a more intensive analysis of the product. Formic acid hydrolysis and two-dimensional chromatography of the DNA components revealed the presence of 5-hydroxymethylcytosine.…”
mentioning
confidence: 97%
“…DNA was extracted with 1 M-HCIO~ at 70°C for 20 min. PENN and SUWALSKI (1969) have claimed that the amount of DNA is underestimated when the usual methods, based on the separation of RNA and DNA by alkaline hydrolysis, are applied to brain tissue. The technique of PENN and SUWALSKI (1969) was therefore compared with that used in the present study and it was found that the amounts of DNA obtained by the two methods were similar (COITERRELL 1971).…”
Section: Animalsmentioning
confidence: 99%